Dakwah Pengurus Masjid Kepada Anak-Anaknya (Studi Kasus Struktur Dkm Masjid Al-Furqon Periode Tahun 2019 - 2023) - Bahrul Ulum Al Ridho; Sudirman Tebba; Muhammad N Abdurrazaq (CV. ITTC INDONESIA, 2023)
The administrators of Al-Furqon Mosque in majority are married and have a family. They are parents in their family. Parents are the firs figure that will influence the personality and thinking pattern of a child. Every parent has their own da’wah way to invite their children into good deeds. The purpose of this research was to find out about (1) the da’wah done by Al-Furqon Mosque Administrators to their children also to find out what factors might support and obstacle factors in its implementation. This research employed qualitative method as the basic of research preparation. The Administrators of Al-Furqon Mosque were as subject, they were the main source of information in the field. Because the problem in the field. Because the problem in the field is usually dynamic/could change (2) then qualitative method became the basic of this research guideline. The researcher was as the instrument in its impelementation, supported by the data collection through recording, previous documents, and interview to the respondents to get additional information needed. Thus the research result obtained from the da’wah of Al-Furqon Mosque Administrators to their children was first they give them exampler, advice, and persuading them persuasively. Then the da’wah supporting factors found by the researcher were the availability of Al-Qur’an, Hadits, Islamic Books, Mass Media, and Islamic School. While the obstacles found were such as smartphone and then less time to be together with their children and difference in opinion.